Is there any increased risk of hypertension, diabetes and cardiac diseases in psoriatic patients with TNF-α G238A and G308A polymorphism? - Işık, Selda; Hiz, Meliha Merve; Kılıç, Sevilay; Öğretmen, Zerrin; SIlan, Fatma (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Psoriasis is regarded as a complex autoimmune disease with strong genetic background. Psoriatic patients suffer from many comorbidities including hypertension, diabetes and cardiovascular diseases. Cytokines such as tumor necrosis factor α (TNF-α) may be a key player that triggers psoriasis and diabetes, hypertension and cardiac disease at the same time. Aim: To evaluate genetic variations in the TNF-α region and its association with psoriasis and related comorbidities. Material and methods : The study covered 129 psoriasis patients with three main subgroups with coronary artery disease (n = 41), hypertension (n = 35), and diabetes (n = 21). DNA samples were genotyped for TNF-α G308A and G238A polymorphisms by real-time polymerase chain reaction melting-curve analysis and results were compared statistically. Results : Psoriatic patients with both TNF-α-298 and TNF-α-308 polymorphisms showed no statistically significant increase in the risk of hypertension (OR = 0.425, χ 2 = 1.76, p = 0.18 and OR = 1.87,χ 2 = 1.33, p = 0.25), coronary artery disease (OR = 1.97, χ 2 = 1.91, p = 0.17 and OR = 2.63, χ 2 = 1.35, p = 0.25), or diabetes (OR = 1.35, χ 2 = 0.24, p = 0.62 and OR = 1.53, χ 2 = 0.24, p = 0.62). Conclusions : The current preliminary results suggested that there was no correlation between TNF- promoter polymorphism and diabetes, hypertension and cardiac disease among psoriatic patients in the Turkish population.